Exploring Junior High School Students’ Experiences in Multimodal Task-Based Language Learning: English - Hidayah, Dahnia Putri; Saefullah, Hilmansyah; Dewi, Indah Purnama (PROJECT (Professional Journal of English Education), 2026)
This study investigates how junior high school students engage with digital multimodal composing (DMC) tasks through a task-based language teaching (TBLT) framework in an English as a Foreign Language (EFL) context. Conducted as a qualitative case study, the research involved classroom observations, interviews, and analysis of students’ digital poster projects. The findings reveal that students approached the multimodal tasks through collaborative planning, negotiation of design, and creative problem-solving using digital tools. While linguistic and technical challenges occasionally hindered their progress, students displayed increasing autonomy, digital awareness, and confidence in expressing ideas through multimodal texts. These results suggest that integrating DMC into TBLT not only strengthens students’ writing competence but also cultivates meaningful participation in digital literacy practices. The study provides insights into how task-based multimodal projects can bridge language learning and digital communication for young EFL learners.